Two, Six, and Twelve-Month Dropout Rate and Predictor Factors After a Multidisciplinary Residential Program for Obesity Treatment. A Prospective Cohort Study - Perna, Simone; Salman, Majeda; Gasparri, Clara; Cavioni, Alessandro; Faliva, Milena Anna; Mansueto, Francesca; Naso, Maurizio; Patelli, Zaira; Peroni, Gabriella; Tartara, Alice; Riva, Antonella; Petrangolini, Giovanna; et al. (Frontiers in Nutrition, 2022)
Obesity is one of the main public health problems in the world and weight loss may be beneficial in terms of reducing risk factors, however, the compliance to the dietary treatment in the long term, could be difficult. The primary aim of the present study is to estimate the dropout rate during a follow-up period of 12 months, following an inpatient multidisciplinary residential program (MRP) for the treatment of obesity. Secondly, predictors associated with the dropout rate are investigated. Adult obese patients who had undergone a MRP for a maximum of 3 months, were followed for 1 year-follow up. Outpatient visits were scheduled at 2, 6 and 12 months after discharge. The study covered 178 subjects, 117 women and 61 men. Both men and women showed an early dropout after 2 months from discharge (21.3%); the dropout rate after 6 months and 12 months were 44.4% and 65.8%, respectively. Concerning predictor factors of dropout, the current analysis concluded that patients who lose weight during the MRP and during the first six months after discharge have a lower risk of dropout at 12 months. Even changes in body composition are predictors of dropout, in fact those who do not see the body composition improved at 6 months, do not continue the follow-up visits. Biochemical parameters, such as values of insulin, HOMA-IR, and uricemia, could affect the dropout rate. Several factors could be predictor of dropout of a dietary treatment, mainly the amount of weight lost during hospitalization.